Bio-Based Aromatic Polyesters Reversibly Crosslinked via the Diels–Alder Reaction - Beljaars, Martijn; Heeres, Hero J.; Broekhuis, Antonius A.; Picchioni, Francesco (Applied sciences, 2022)
Diphenolic acid is functionalized with furfuryl amine and subsequently incorporated in a (partly) bio-based polyester through interfacial polycondensation with terepthalic chloride. The furan groups present in the resulting polyester are able to form a thermoreversible covalent network with different bismaleimide moieties via the Diels–Alder (DA) reaction. Our analysis of the polymer network by 1H-NMR clearly shows the formation of both possible stereoisomers (endo and exo) from the Diels–Alder coordination of furan and maleimide. Furthermore, it was found that these isomers can be reversibly interchanged at temperatures below the reported retro Diels–Alder reaction temperature, a phenomenon often claimed but, until present, never directly observed, for thermally reversible polymeric systems. Finally, a proof of principle for reversibility and recyclability is shown.